Community outreach and engagement in the time of COVID 19: Efforts & approaches of academic libraries - Peñaflor, Janice D.C. (Animo Repository, 2021)
Objective. This paper aims to investigate the types and scope of community engagement and outreach activities of academic libraries while the physical library spaces remain closed or operating on a limited capacity. It also looks at the tools and methods employed to implement such activities. The paper also attempts to uncover patterns or emerging themes as libraries explore innovative ideas and take new initiatives for the betterment of the community they serve. Methods. The study employs a website and Facebook page survey of AUN (ASEAN University Network) Inter-Library Online (AUNILO) member-libraries. The following six outreach categories will be utilized: (1) Collection-Based Outreach; (2) Instruction & Services-Based Outreach; (3) “Whole Person” Outreach; (4) Just for Fun Outreach; (5) Partnerships and Community-Focused Outreach; and (6) Multi-Pronged Themed Events and Programming. Said categories were derived from Farrell and Mastel (2016) paper entitled “Considering Outreach Assessment: Strategies, Sample Scenarios, And A Call to Action.” Results. Findings of the study will offer some insights on how libraries strengthen their roles in transforming societies as they provide opportunities to bring about positive change in their communities. Moreover, this paper will also challenge libraries to take a closer look at their own activities and consider how they can design creative and inspiring ways to connect with their communities. Conclusions. In response to the COVID-19 crisis, libraries are proactively pivoting their community engagement and outreach efforts online and are finding new ways to serve faculty, students, and partners. Libraries are committed to strengthening the resilience and recovery of the community through working collaboratively with its members and building partnerships with relevant organizations.